Podcasts: An Innovative Teaching-Learning Experience for High School Students in Antofagasta to Reflect on Their Post-COVID Experiences. (Innovaciones Educativas, 2024)
This article presents a teaching experience based on good practice and innovation that explores the use of podcasts as a pedagogical strategy in the teaching-learning process. The experience consisted of a series of podcasts created by eighth grade students from the city of Antofagasta, Chile, in which they shared their experiences and reflections after the COVID-19 confinement. The methodology was implemented during an intensive and voluntary extracurricular workshop that took place from 7 to 11 November 2022. The students learned all the elements that make up the radio language to create podcasts. They also learned how to edit their radio productions and listened to and commented on their podcasts in groups to understand the usefulness of this format in their own processes. In this way, they became familiar with the radio format, created scripts, recorded, edited and listened to their own productions. The result was nine podcasts. Although the initial topics varied, the activity was positively evaluated by the students, confirming its effectiveness. It is therefore a significant contribution to pedagogical change, providing students with a new tool to produce their own content. From this experience it can be concluded that this tool can be useful for both teachers and students, provided that it is based on a didactic planning process. It is crucial to bear in mind that the podcasts must be driven by the students' intrinsic motivation, avoiding an external and adult-centred perspective.
Keywords: Educational Radio; Media Education; Digital Literacy; Educational Technology